Produção de ferro-gusa e escória vanadífera a partir de rejeitos da Mineração Caraíba - Thiago Vitali Pignaton (2010)
This investigation addressed the recovery of magnetite and vanadium pentoxide disposed at Mineração Caraiba SA (MCSA) tailings pond via a route comprising magnetic separation and pirometallurgy aiming at achieving the products pig iron and vanadiferous slag. MCSA´s tailings pond extends at approximately 700 ha and holds 71 million tons oftailings containing 3% to 4% magnetite and 0.05% vanadium pentoxide. The study suggested hydraulic dismount followed by pumping to transport the material from the pond to the beneficiation plant.Magnetic separation is the best concentration option due to the ferrimagnetic characteristic of magnetite. The concentration route consists of a rougher low intensity magnetic separation (LIMS) stage, a regrinding stage for magnetite liberation, requiring 12 kWh/t energy consumption, followed by two cleaner stages for the concentrateenrichment, leading to, respectively, 60% iron and 0.75% V2O5 grades in the concentrate, at 80% magnetite recovery and 40% to 50% vanadium pentoxide recovery levels. The vanadium recovery depends on the amount associated with magnetite. The sintering studies showed that the magnetic concentrate responds well to the process leading to 8% RDI<2.8mm, RI between 52% and 54%. Despite the fine size distribution(P80 at 40 m), with the use of special mixers, lime, charcoal and 8% moisture content the adequate formation of micropellets in a cold process was achieved. The reducing smelting studies led to high levels of Fe and V recovery to the pig iron, above 95%, at iron grades above 90% and vanadium content 0.5%. In the slag formation stage (O2 injection), the purified pig iron reached 97% iron grade at low contaminantscontents, but the slag presented low V2O5 grades, reaching only 3%, well below the expected level 25%, despite the high V recovery, above 95%, probably due to the high Fe and Cr grade in the slag, caused by a high O2 injection rate.